Volumetric and compressibility studies for (L-arginine + D-maltose monohydrate + water) system in the temperature range of (298.15 to 308.15) K. (2nd September 2016) - Kumar, Ashwani; Rani, Ruby; Gupta, Anjana; Saini, Balwinder; Bamezai, Rajinder K
ABSTRACT: The density and speed of sound of L-arginine (0.025–0.2 mol kg −1 ) in aqueous + D-maltose (0–6 mass% of maltose in water) were obtained at temperatures of (298.15, 303.15 and 308.15) K. The apparent molar volume, limiting apparent molar volume, transfer volume, as well as apparent molar compressibility, limiting apparent molar compressibility, transfer compressibility, pair and triple interaction coefficients, partial molar expansibilities, coefficient of thermal expansion and also the hydration number, were calculated using the experimental density and speed of sound values. The results have been discussed in terms of solute–solute and solute–solvent interactions in these systems. Solute–solvent (hydrophilic–ionic group and hydrophilic–hydrophilic group) interactions were found to be dominating over solute–solute (hydrophobic–hydrophilic group) interactions in the solution, which increases with increase in maltose concentration.